Kosmos kak predchuvstvie - Uchitel, Alexei (Russia : Uchitel, Alexei ; Saksaganskaya, Kira, 2005)
The film is set in 1957 in a small port town on the edge of the Soviet empire. The bright beaming eyes of Konyok and Lara - a simple-hearted restaurant cook and his waitress girlfriend - follow the movement of the first sputnik with delight. The film’s main protagonist is a “simple Soviet man.” His alter-ego, friend-enemy, the mysterious Gherman with a strange name and even stranger behavior appears out of nowhere and is prepares to escape from the Soviet Union. He practices sports, swims in icy water, learns a single English phrase about political asylum, and finally seduces Konjok’s girlfriend in order to gain access to foreign ships.
Duration: 01:26:00
Keywords: Fiction films